The Uncertainty of Transnational Parenthood and Anti-System Political Preferences - DIMA, Ana Maria (2026)
Migration is one of the defining phenomena of today’s changing world (Castels, De Haas, Miller 2014, Collier 2014). Population movement is a natural historical occurrence, but in our current society it is being heavily politicized and regulated in ways that challenge traditional ways of living. The opposition between people who leave versus those who stay boils down to a dichotomy between traditional lifestyles and life-changing lifestyles part of late modernity, with the latter being more impacted by uncertainty. Major events such as Brexit and the election of President Trump in 2016, have shaken up the world order as known and also led to an increase in illiberalism and far-right discourses, particularly in Western Europe, where the German AfD has noticed a rise in their ranks, or the Italian Fratelli d’Italia’s rise to power.